Pengembangan Lembar Kerja Peserta Didik Berbasis Multikultural Pada Pembelajaran Seni Budaya dan Prakarya Kelas V Sekolah Dasar - Febri Yana Riza; Zariul Antosa; Gustimal Witri (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This research aims to develop multicultural-based LKPD on SBDP learning in grade V elementary schoo and aims to test the feasibility of multicultural-based LKPD that has been used by students of grade V SDIT Raudhaturrahmah Pekanbaru in March 2021. This type of research is research development R&D (Research and Development) using a 4D model consisting of 4 stages namely Define, Design, Development and Disseminate. Validation results from experts obtained an overall average at draft 1 of 81.37 with a valid category. The average overall validator rating score in draft 2 is 96.55 with a very valid category. The average assessment score of the overall teacher response questionnaire is 92.5 with a very decent category. Meanwhile, the average assessment score of the overall response of students was 94.78 with a very good category. Based on the data, multicultural-based LKPD is very feasible to be used in SBDP learning in grade V elementary school.